The Role and Legal Basis of Ethical-Psychology in Working with Citizens During the Service of the Employees of the Internal Affairs Bodies - Lepesov A.G. (Zien Journals, 2022)
Organization of moral-psychological units in the field in order to increase the moralpsychological awareness of the employees of internal affairs bodies.
Keywords: Internal affairs bodies; moral-psychological; manners; stress